Argumentative Techniques in the Poetry of Al-Abbas Ibn Mirdss Al-Salami - Ashqar, Sahar Ḥasan Abdulqadir (Arts for Linguistic & Literary Studies, 2025)
This article investigates how Al-Abbas ibn Mirdss Al-Salami structures persuasion in his verse. It is organized into an introduction, a brief preface, and three analytical sections. Using a pragmatic-argumentative lens, it shows that the poet leans heavily on linguistic devices—chiefly repetition—to steer audience reception. Lesser but notable tools include opening particles, causal markers, interrogatives, and oaths. Complementing these are rhetorical figures (illustrative exempla, metonymy, antithesis) and quasi-logical moves, all of which sharpen the argumentative edge of his poetry. The study thus confirms that Al-Abbas’s diction, imagery, and reasoning work in concert to transform poetic utterance into an act of strategic persuasion.